2018
DOI: 10.1038/s41386-018-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plasma cytokines on kynurenine and kynurenic acid in schizophrenia

Abstract: Abnormalities in the kynurenine pathway (KP) of tryptophan degradation, leading to the dysfunction of neuroactive KP metabolites in the brain, have been implicated in the pathophysiology of schizophrenia (SZ). One plausible mechanism involves dysregulation of various pro-inflammatory cytokines associated with the disease, which affect indoleamine-2,3-dioxygenase (IDO), a key enzyme for tryptophan to kynurenine conversion. In order to test this hypothesis directly, we measured plasma levels of the major KP meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 48 publications
5
23
4
1
Order By: Relevance
“…This decrease in KYNA contrasts with previous reports in CSF and postmortem brain tissue where increased KYNA levels in patients with BD were related to manic episodes and psychotic symptoms . In line with our findings, studies using peripheral blood samples showed unchanged or decreased KYNA levels in patients with a history of mania or psychosis . Decreased peripheral KYNA levels have also been shown in euthymic and depressive patients with BD .…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…This decrease in KYNA contrasts with previous reports in CSF and postmortem brain tissue where increased KYNA levels in patients with BD were related to manic episodes and psychotic symptoms . In line with our findings, studies using peripheral blood samples showed unchanged or decreased KYNA levels in patients with a history of mania or psychosis . Decreased peripheral KYNA levels have also been shown in euthymic and depressive patients with BD .…”
Section: Discussionsupporting
confidence: 71%
“…However, in patients with psychiatric disorders, the interaction between inflammation, kynurenine metabolism, and clinical symptoms is little investigated. In CSF of patients with schizophrenia, IL‐6 levels were negatively correlated with the TRP/KYNA ratio, however a study with larger sample size could not confirm an effect of cytokines levels on kynurenine metabolism disturbances . In depressive populations such a link between inflammation, kynurenine metabolism, and depressive symptoms has not yet been shown …”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations